Caries Assessment by ORATEST in school going children: A cross sectional study - Umeed Jawaid, Shama Asghar, Meisha Gul, Ayesha Zafar (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine caries activity among school going children using an uncomplicated oral rinse test (Oratest) Method: A Cross-sectional study was conducted in the Paediatrics Dentistry department of Bahria University Dental College Karachi, Pakistan from July 2019 to October 2019. Out of total 300 children visiting paediatrics dental clinic of private dental college, Karachi, Pakistan between July 2019-Oct 2019, 200 children were excluded who did not meet the inclusion criteria. Out of remaining 100 children, randomly selected 25 children were allocated to test group and separate 25 healthy children without caries were allocated to control group. On the basis of number of decayed teeth, the test group was divided into three subgroups: Group-I had 1-2 carious teeth, individuals with 3-5 carious lesions were included in Group-II, while 7-9 were included in Group-III. Microbial status was evaluated using Oratest. The time observed for the change colour represents the microbial activity, it was documented in planned proforma. Results: A total of 50 children, 26 were female and 24 were male with a mean age of 6.74 ±2.20 yrs. were included. The result showed significant relationship between control and test group in term of mean time for Colour modification and number of carious lesion. The Oratest colour change time was higher in patients with less number of carious teeth, showing an inverse relationship between Oratest and presence of caries lesions. The result also showed a significant relationship between age and eruption status of molar with caries activity. Conclusion: Caries activity can be assessed using Oratest as it is an uncomplicated, economical, chairside and time efficient test. It can be of immense service in aiding caries activity assessment in paediatric dental setups as it is gladly accepted by children. The Oratest can be used as a teaching tool to improve the oral health literacy of the children and their families, by viewing the activity of their bacteria. Keywords: Caries detector, dental caries, microbial colonies, oratest